Reproduction and Development in Fish: Solving Bottlenecks in Modern Aquaculture - Renato Massaaki Honji; Paulo Henrique de Mello; Bruno Cavalheiro Araújo (Animals)
The aquaculture industry is home to the fastest-growing activity in the agriculture sector worldwide and is one of the leading sectors in global food production [...]